The Impact of Information and Communication Technology on Carbon Emissions in Emerging Markets - Tsaurai, Kunofiwa; Chimbo, Bester (International Journal of Energy Economics and Policy, 2019)
This study explored the influence of information and communication technology (ICT) on carbon emissions in emerging markets using panel data analysis methods (fixed effects, random effects, pooled OLS, FMOLS) with annual secondary data spanning from 1994 to 2014. Additionally, the study investigated whether financial development and economic growth are channels through ICT has an influence on carbon emissions. Without interaction terms, ICT was found to have had a significant positive influence on carbon emissions across all the four panel data analysis methods. After introducing interaction terms, financial development was found to be a channel through which ICT increased carbon emissions under the fixed effects, random effects and the FMOLS. Under the pooled OLS, financial development was found to be a channel through ICT enabled the reduction in carbon emissions. Economic growth was found to be a channel through ICT lowered down carbon emissions in emerging markets across all the four panel data analysis methods. Keywords: Information and Communication Technology, Carbon Emissions, Financial Development, Growth, Emerging Markets JEL Classifications: N7, P2 DOI: https://doi.org/10.32479/ijeep.7677